Women's fashion and innovation policies: Inequalities in the Agreste Pernambucano Apparel Hub Complex: desigualdades no Polo de Confecções do Agreste Pernambucano (PerCursos, 2025)
This article analyzes how different women's fashion producers in the Agreste Pernambucano Apparel Hub access public policies to encourage innovation, including financial resources and technical support. The research, carried out in 2018 as part of the author's doctoral thesis, involved a bibliographical survey, field observation and 47 interviews with womenswear producers and representatives of institutions working in the cluster. The results show that there are inequalities in access to technical and financial incentives in the territory, indicating that the more established producers benefit disproportionately from these resources. On the other hand, the majority - made up of unregistered micro and small production units with low capitalization capacity - face structural obstacles that limit their inclusion and permanence in development policies. This dynamic reveals the fragility of relationship networks and the need for state intervention to mitigate growing socio-territorial inequalities.
Keywords: socioeconomic inequalities; clothing; innovations